Debt Report 2020 Edition III - World Bank (World Bank, Washington, DC, 2020)
This is the third in the series of Debt Reports for 2020 published online, at regular intervals, over the course of the year. Their aim is to provide users with analyses of evolving trends and developments related to external debt and public debt in individual countries and regional groups, with primary emphasis on low- and middle-income countries, and to keep users abreast of debt-related issues and initiatives.